The Improvement Critical Thinking Ability of Students Through Reciprocal Learning (Reciprocal Teaching) and Jigsaw Models in Biological Lesson in Parlaungan Islamic High School and Al-Muslim High School - Slamet Slamet; Djoko Adi Walujo; Sugito Sugito (PROGRAM STUDI PENDIDIKAN BIOLOGI FAKULTAS KEGURUAN DAN ILMU PENDIDIKAN UNIVERSITAS JEMBER, 2019)
Reciprocal teaching is one of learning model which is consist of four strategies: summarizing, questioning, claryfying the knowladge, and predicting. Another type of cooperative learning is jigsaw models. Jigsaw is a cooperative learing model which create some expert learning groups to stimulate critical thinking of the student abilities. Jigsaw is a learning model that triggers student to have active role in group learning. This study was to know the effect of Reciprocal Teaching with Jigsaw learning model on student critical learning ability is important to be exposure because its study shows that the 10th grade high school students had a low critical thinking abilities. As pre-test and post-test statistical data showed the influence of prior knowledge on learning result has significance points of 0,443 > 0,05., so it can be conclude that the data is significant. Based on the data, there are influence between the prior knowledge to the crtitical thinking ability result. According to the statistical data, the influence of learning models on learning results has significance points of 0,060 > 0,05., so it can be conclude that there are diffrence effect in critical thinking ability by using Reciprocal teaching vs Jigsaw models. Based on the data, the significance points are 0,126 > 0,05., it indicates that the students learning results data is valid or significant and it can be conclude that there are some interaction between Reciprocal teaching with Jigsaw model learning method and aperception knowledge on the learning result of 10th grade student critical thinking ability at Islam Parlaungan High School Waru and Al-Muslim High School Waru.